Smart Drip Infusion Monitoring System and Electronic Valve System with Quantitative Control Using IoT - Gupta, Akash Das; J, Rakshitha; LD, Lavanya; M, Meenakshi; Patil, Vijayalaxmi R (International Journal of Computer Sciences and Engineering, 2025)
In health care system environment use of IOT technologies bring convenience to both doctors and patients. This work proposes a method for drip infusion monitoring system. The system is designed to work in two modes viz Manual mode and Auto mode. The patient’s heart beat and body temperature are obtained using sensors. Based on these readings the flow rate of the glucose is determined by the doctor or nurse. While the glucose is being given to t he patient, it should be carefully monitored so that the glucose bag does not become empty. This is very much essential to prevent reverse blood flow. In this project the reverse blood flow is prevented using solenoid valve with quantitative control. The salient features of this project includes: Drip bottle weight monitoring using a load cell , Flow control using a electronic valve, Patient Monitoring using Sensors and Automation of Drip Process.